Upaya Peningkatkan Hasil Belajar Mata Pelajaran Bahasa Arab Melalui Media Audio Visual Pada Peserta Didik Kelas Iv Madrasah Ibtidaiyah Taman Islam Cibungbulang Bogor - Rifa Rindiani; Tita Hasanah (JURNAL KAJIAN ISLAM MODERN, 2022)
The aim of this research is to determine the application of using the audio-visual media to improve the result of learning in arabic subjects of Madrasah Ibtidaiyah Taman Islam Bogor and the respondents are 35 respondents. The research method that used is the classroom research method. The method isu sing cycles, each cycle consist of fourth steps. First is planning, second is implementation, third is observation, and fourth is reflection. While the collection of data used the observation, test, and documentatoin. The indicator of the research successful is when the students are achieve of 70 maximum graduation criteria. Arabic learning is used the audio-visual media has increased outcomes learning. It showed by the students result. In pre-test questions is 45,71. Then after doing the first cycle is 53,14 (post- test II). In second cycle is 71,42 (post-test II). Based on the result of this research is concluded that arabic learning using the audio-visual media is improving the result learning of grade IV students in Madrasah Ibtidaiyah Taman Islam Cibungbulang Bogor. In academic year 2018/2019.